1990
DOI: 10.1136/pgmj.66.779.720
|View full text |Cite
|
Sign up to set email alerts
|

Gastric antral vascular ectasia (watermelon stomach)—therapeutic options

Abstract: Summary: We have encountered five cases of chronic iron deficiency anaemia due to bleeding from gastric antral vascular ectasia (watermelon stomach). Two cases were associated with a lymphoma and in three cases there was evidence of portal hypertension. Two patients were treated conservatively by blood transfusions. The other patients required either surgery or tranexamic acid or endoscopic laser therapy to control the chronic haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 15 publications
1
28
0
5
Order By: Relevance
“…Initially corticosteroids were used to treat GAVE and case reports showed that 4 out of 11 patients responded to this measure [2,25,26,27,28,29,30,31, 34,36,37,38]. Typical steroid side effects, like steroid-induced diabetes mellitus and/or cushing-like illness, limit its use.…”
Section: Therapymentioning
confidence: 99%
“…Initially corticosteroids were used to treat GAVE and case reports showed that 4 out of 11 patients responded to this measure [2,25,26,27,28,29,30,31, 34,36,37,38]. Typical steroid side effects, like steroid-induced diabetes mellitus and/or cushing-like illness, limit its use.…”
Section: Therapymentioning
confidence: 99%
“…Few case-reports have suggested a potential benefit from the use of tranexamic acid but reported severe side effects (central venous stasis retinopathy; deep venous thrombosis and pulmonary embolism) limit its use [46][47][48] . A case-report showed complete resolution of GAVE with intravenous infusion of methylprednisolone and cyclophosfamide in a patient with associated systemic sclerosis and pernicious anaemia [49] ; but, such result has not been yet confirmed in larger series.…”
Section: Medical Therapymentioning
confidence: 99%
“…In cirrhosis-associated GAVE, correction of portal hypertension with beta-blockers or transjugular intrahepatic portosystemic shunt has not resulted in a reduction in the incidence of bleeding episodes and transfusion requirements (8,14). Other medical therapies that were used, with variable success rates, include corticosteroids (15 -17), tranexamic acid (18,19) and thalidomide (20).…”
Section: Discussionmentioning
confidence: 99%